A Dictionary of computing (Oxford, 1997)
This book contains nearly 6,000 entries and a comprehensive cross-reference system. It reflects in all aspects of computing, especially in personal computing, computer graphics, networking, artificial intelligence, and computer security
Keywords: Computer science